Temel hak ve özgürlüklerin güvence ölçütü olarak demokratik toplum düzeninin gerekleri - Eren, Abdurrahman (My University, 2002)
1982 Anayasası'nın 13. maddesinde, temel hak ve özgürlüklere ilişkin sınırlamaların demokratik toplum düzeninin gereklerine aykırı olamayacağı ifade edilmektedir. İnsan Hakları Avrupa Sözleşmesine taraf bir ülke için, demokratik toplum düzeninin gereklerine ilişkin standartlar minimum ölçülerle Sözleşmede tanınmakta ve İnsan Hakları Avrupa Mahkemesi içtihatlarıyla sürekli gelişmektedir. Bu standartlara uymak Sözleşmenin öngördüğü denetim kapsamında, taraf ülkeler açısından bir yükümlülüktür. Dolayısıyla temel hak ve özgürlüklere ilişkin sınırlamaların demokratik toplum düzeninin gereklerine uygunluğu, minimum ölçülerde, Sözleşme'yle birlikte belirlenmelidir. Bu çalışmada temel hak ve özgürlüklerin güvence ölçütü olarak demokratik toplum düzeninin gerekleri İnsan Hakları Avrupa Sözleşmesi ile öngörülen ortak güvence sistemi içerisinde incelenmektedir. Birinci bölümde, ortak güvence sisteminde pozitif temelleri incelenirken; ikinci bölümde, ilkenin içtihadi alanda nasıl yorumlandığı ve uygulandığı üzerinde durulmaktadır. Sonuç olarak, Anayasal şikayet yolunun ortak demokratik toplum anlayışının paylaşılmasında önemli bir etkileşim aracı olacağı önerilmektedir.

In article 13 of the Constitution of 1982 it has been stated that the restrictions concerning the fundamental rights and freedoms could not be contrary to the requirements of democratic society order. For a country, signatory of European Convention of Human Rights, the standarts concerning the requirements of the society order are acknowledged in the Convention with minimum measures and are developed by the European Human Rights Court jurisprudences. Abiding by these standartd is a requirement for the signatory countries within the framework of the control anticipated by the Convention. Therefore, the conformity of the restrictions concerning the fundamental rights and freedoms to the requirements of democratic society order should be determined together wiht the Convention, in minimum measures. In this study, the requirements of democratic society order as a warranty criterion of the fundamental rights and freedoms are examined within the common warranty system anticipated with European Convention of Human Rights. While the positive fundamentals in the common warranty system are examined in chapter 1, how the principle is interpreted and applied in the field of jurisprudence is emphasized in chapter 2. Finally, it is suggested that constitutional medium of complaint will be a considerable means of interaction of sharing the common democratic society mentality.
Keywords: Demokrasi Türkiye; Kamu Hukuku_Türkiye; Özgürlük